1993
DOI: 10.1038/364639a0
|View full text |Cite
|
Sign up to set email alerts
|

Ruffles induced by Salmonella and other stimuli direct macropinocytosis of bacteria

Abstract: Ruffles are specialized plasma membrane ultrastructures of mammalian cells though to be integral to growth, development and locomotion. Induced by growth factors, mitogens or oncogene expression, ruffles are sites of filamentous actin rearrangement and are temporally associated with enhanced pinocytosis. But the function of ruffles, their mechanism of induction and their role in pinocytosis are not understood. We have observed formation of structures resembling ruffles associated with the site of entry of inva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
306
2
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 413 publications
(324 citation statements)
references
References 28 publications
14
306
2
2
Order By: Relevance
“…5, A and B). At this time point extensive membrane ruffling, characteristic of Salmonella invasion, is evident where the bacteria are in contact with the host cell (29). Bacterial-induced translocation of Akt is still evident 30 min post-infection, which is similar to the localization pattern induced by cell-cell or cellmatrix contact in epithelial cells (22).…”
Section: Pi3-k Activation and Rapid Translocation Of Akt To The Plasmsupporting
confidence: 54%
“…5, A and B). At this time point extensive membrane ruffling, characteristic of Salmonella invasion, is evident where the bacteria are in contact with the host cell (29). Bacterial-induced translocation of Akt is still evident 30 min post-infection, which is similar to the localization pattern induced by cell-cell or cellmatrix contact in epithelial cells (22).…”
Section: Pi3-k Activation and Rapid Translocation Of Akt To The Plasmsupporting
confidence: 54%
“…Coupled with its propensity to invade cultured epithelial cells, this makes it an extremely valuable tool for studying invasion and intracellular survival and has enabled the identi®cation and characterization of many of the factors involved (Finlay and Falkow, 1990;Francis et al, 1992;Galan et al, 1992;Ginocchio et al, 1992;1994;Garcia-del Portillo et al, 1993a;1995;Stein et al, 1996;Hardt et al, 1998). Initial contact of Salmonella with an epithelial cell induces host cell signal transduction cascades and extensive cytoskeletal rearrangements, which lead to the formation of membrane ruf¯es on the cell surface (Finlay et al, 1991;Ruschkowski et al, 1992;Francis et al, 1993;Pace et al, 1993). Ruf¯e formation is mediated by a host cellular pathway that is dependent on the small GTP-binding protein CDC42 and a bacterially encoded Rho GTPase activator, and results in the internalization of bacteria into a unique membrane-bound vacuole (Finlay and Falkow, 1990;Garciadel Portillo et al, 1994;Chen et al, 1996;Hardt et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Salmonella spp. induce their own uptake in macrophages by stimulating cell membrane ruffling [42,43]. In some experiments, cattle DC were incubated for different times with S. typhimurium (strain BRD562) at a ratio of 1:10 together with LY.…”
Section: Tracer Endocytosismentioning
confidence: 99%